Improving the Performance of Band Saws by Local Thermophysical Effects on the Blade - Vladimir I. Melekhov; Ivan I. Solovev; Ekaterina V. Sazanova; Natalya G. Ponomareva (Лесной журнал)
The performance of a band saw is largely determined by stability and durability – the ability to maintain operational properties for a long time under the influence of external and internal factors until the onset of a limiting state, ending with loss of stability and destruction of the saw blade. During operation, the band saw blade is subject to the complex effects of force and temperature factors that change its stress state. The durability and stability of a band saw depends on the magnitude and nature of the distribution of total stresses in the most loaded cross-section of the blade. The final stress on the section of the blade, determined by the cross section, is the sum of internal stresses and external forces: saw tension, bending of the blade on the pulleys, centrifugal forces, blade rolling, blade heating, pulley tilt, cutting forces, and other unaccounted stresses. Numerous studies have established that the destruction of band saws is of a fatigue nature, caused mainly by the accumulation of stresses in the saw blade under the influence of constant blade tension forces and alternating cyclic bending stress of the blade on the pulleys. One of the ways to increase the durability of a band saw is to reduce the amplitude of cyclic bending stresses in the blade by creating internal compensating counter-directional stresses. As a result of the analysis given in the article of the methods for creating internal compensating stresses in a band saw by mechanical or long-term high temperature exposure to the entire saw blade, it has been noted that such approaches limit the durability of the tool, reduce the hardness of the material and the durability of the cutting edge of the saw tooth. It is proposed to form fields of internal residual compensating stresses in the band saw blade by thermophysical effect, which consists in creating local fields of residual stresses in the saw blade by a short-term (1–2 s) concentrated thermal action on an array of alternating mini-strip sections located transversely along the saw blade.